Simulation analysis and experimental study of milling surface residual stress of Ti-10V-2Fe-3Al. (April 2018) - Wu, Qiong; Xie, Dong-Jian; Si, Yu; Zhang, Yi-Du; Li, Lei; Zhao, Ying-Xin
Graphical abstract: Abstract: Nowadays, Ti-10V-2Fe-3Al is widely used in aerospace field because of its high specific strength, good breaking property, low forging temperature, and excellent stress corrosion resistance. However, these properties render Ti-10V-2Fe-3Al a hard-to-cut material. Moreover, the low thermal conductivity of Ti-10V-2Fe-3Al results in high temperature on the tool face, which causes the wear of cutting tool. This paper presents a simulation analysis and an experimental validation on the milling surface residual stress of Ti-10V-2Fe-3Al. The formation mechanism and influence of cutting parameters on the residual stress in the end milling of Ti-10V-2Fe-3Al are investigated through orthogonal experiments. The interaction effect of cutting parameters on forming residual stress is studied by analyzing the finite element (FE) simulation results. Moreover, relevant experiments are carried out to validate the accuracy of FE simulation. On the basis of these data, a formulation describing the interaction effect is proposed.